Occurrence of aetokthonotoxin producer in natural samples - A PCR protocol for easy detection - Štenclová, Lenka; Wilde, Susan B; Schwark, Markus; Cullen, Jeffrey L; McWhorter, Seth A; Niedermeyer, Timo H J; Henderson, W Matthew; Mareš, Jan (Harmful algae, 2023)
Cyanobacteria are well known producers of bioactive metabolites, including harmful substances. The recently discovered "eagle killer" neurotoxin aetokthonotoxin (AETX) is produced by the epiphytic cyanobacterium Aetokthonos hydrillicola growing on invasive water thyme (Hydrilla verticillata). The biosynthetic gene cluster of AETX was previously identified from an Aetokthonos strain isolated from the J. Strom Thurmond Reservoir, Georgia, USA. Here, a PCR protocol for easy detection of AETX-producers in environmental samples of plant-cyanobacterium consortia was designed and tested. Three different loci of the AETX gene cluster were amplified to confirm the genetic potential for AETX production, along with two variable types of rRNA ITS regions to confirm the homogeneity of the producer´s taxonomic identity. In samples of Hydrilla from three Aetokthonos-positive reservoirs and one Aetokthonos-negative lake, the PCR of all four loci provided results congruent with the Aetokthonos presence/absence detected by light and fluorescence microscopy. The production of AETX in the Aetokthonos-positive samples was confirmed using LC-MS. Intriguingly, in J. Strom Thurmond Reservoir, recently Hydrilla free, an Aetokthonos-like cyanobacterium was found growing on American water-willow (Justicia americana). Those specimens were positive for all three aet markers but contained only minute amounts of AETX. The obtained genetic information (ITS rRNA sequence) and morphology of the novel Aetokthonos distinguished it from all the Hydrilla-hosted A. hydrillicola, likely at the species level. Our results suggest that the toxigenic Aetokthonos spp. can colonize a broader array of aquatic plants, however the level of accumulation of the toxin may be driven by host-specific interactions such as the locally hyper-accumulated bromide in Hydrilla.
Keywords: polymerázová řetězová reakce; Polymerase Chain Reaction; Justicia; Hydrilla; rRNA ITS; Mass Spectrometry; Chromatography, Liquid; jezera; Cyanotoxin; Vacuolar myelinopathy; hmotnostní spektrometrie; chromatografie kapalinová; Aetokthonos; Lakes